Traffic engineering of IP/GMPLS over WDM - Shaaya S.A.; Ibrahim W.M.W.; Din N.M. (2023)
The GMPLS over WDM network is seen as a very promising network solution for meeting the ever-increasing Internet users multimedia demands. Such a network has the capability of providing quality of service in terms of the information throughput, transfer speed and smoothness of transmission. This paper investigates the performance of an IP with GMPLS network over WDM with a constraint, i.e. the availability of lambda. This is conducted using simulation. The simulation work is done using an source network simulator, known as NS-2. A GMPLS WDM network was modeled and a performance study based on the throughput, end-to-end delay, jitter and lambda utilization of the network are presented in this paper. 2005 IEEE.